Improving the Quality in Indian Higher Education Using Lean Six Sigma - et al., MR. P. SURESH KUMAR (International Journal of Control and Automation, 2019)
Education is the only process which is key feature for human kind to evolve them in this wonderful universe. There are number of properly structured approaches to educate. Different stake holders are involved to produce a successful cycle of education for people. In India there are different levels of education according the age of person and the successful completion of their levels in respective cycle of education. As country India is having huge amount young age people population. The most important task of the society is to guide this huge young member to enrich their knowledge in all means. Now this is the big challenge of academicians to achieve this daunting task with high quality. Even then the government is approaching this matter with lot of efforts by providing lot of standards to its vendors in the name of different agencies. Yet the meeting of quality in all form of process is a hindrance.